An Integrated Approach to Pressure Ulcer Prevention and Treatment: The Role of Physical Activity, Nutrition, Care and Modern Technologies. - Piotr Mól; Małgorzata Łabuś; Karol Krzykawski; Antoni Sieńko; Julia Dołęga; Patrycja Hudzińska; Bartłomiej Zabawa; Tomasz Maciejczyk; Łukasz Stanisław Papież; Jakub Sadowski (Journal of Education, Health and Sport)
Introduction: Pressure ulcers represent a significant healthcare challenge affecting patient outcomes and quality of life. This comprehensive review examines the integrated approach to pressure ulcer prevention and treatment, focusing on physical activity, nutrition, modern wound care technologies, and emerging therapeutic strategies.